Depictive Hand Gestures as Candidate Understandings. Issue 2 (3rd April 2022) - Jokipohja, Anna-Kaisa; Lilja, Niina
ABSTRACT: This article uses multimodal CA to analyze depictive hand gestures that are used to check understanding of the co-participant's preceding action. Drawing on data from cooking and farming interactions, the analysis scrutinizes how depictive gestures come to be treated as other-initiations of repair. The analysis shows that relevant factors in this are: (a) the gesture's design, i.e., its form and movement in relation to the material ecology of the interaction, including relevant objects; (b) the gesture's position and timing in the unfolding sequence; (c) the embodied participation framework, including the body positions and gaze patterns of all participants; and (d) the participants' shared knowledge and understanding of the broader activity context, including their familiarity with the ingredients and dishes in-the-making. The analysis contributes to research on gestural depiction in human meaning making and to the study of embodiment in repair organization. The data are in Finnish with English translations.